Effects of oral administration of peptides with low molecular weight from Alaska Pollock (Theragra chalcogramma) on cutaneous wound healing - Tingting Yang; Kai Zhang; Bafang Li; Hu Hou (Journal of Functional Foods, 2018)
Protein supplements play an important role in wound healing. The effect of collagen peptide (PCP) and flesh protein peptide (FPP) from Alaska Pollock on wound healing was investigated. The molecular weight distributions of PCP and FPP were in a range of 430–1000 Da and 100–1000 Da, respectively. Compared to vehicle group, the wound healing activities in PCP and FPP were significantly enhanced, which could be corroborated by the increase of wound healing rate, hydroxylproline content, and tensile strength in rat wound model (P < 0.05). H&E showed a near-normal epidermis structure of PCP and FPP on day 12, but vehicle group displayed poor re-epithelialization. PCP and FPP increased the levels of bFGF, EGF, TGF-β1 and TβRII (P < 0.05), and decreased the content of Smad7 in TGF/Smad signaling pathway. Therefore, FPP and PCP can be used as effective ingredients in the treatment of wound healing.